ANALISIS OPINI AUDIT GOING CONCERN: PREDIKSI KEBANGKRUTAN, LEVERAGE DAN PERTUMBUHAN PERUSAHAAN PADA PERUSAHAAN PERBANKAN DAN PEMBIAYAAN YANG GO PUBLIC DI BEI - Nursasi, Enggar; Maria, Evi (Faculty of Economics Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2013)
The purpose of this study to prove whether banks and finance companies that go public on the Stock Exchange for the period 2009–2011 with the reception an unqualified opinion with an explanatory paragraph going concern enterprise, influenced by the prediction of bankruptcy , the low value of the company‘s leverage ratio , which means assets owned more slightly compared with corporate debt and falling growth. The data used are secondary data from financial reports issued by independent auditors. In this study , there are two variables is the dependent variable in the form of going concern audit opinion and independent variables such as bankruptcy prediction , leverage and growth companies. Sample criteria are banking and finance company that is consistently in IDX listings from 2009 to 2011, which contained the independent auditor’s report on the financial statements of the company respectively . Data analysis was performed using a hypothesis test with Partial Least Square (PLS) by reason of the samples in this study was very small (N = 15) , the data are not normally distributed and independent variables (going concern opinion) has a nominal size scale. The analysis shows that significant bankruptcy prediction variables, the variable Leverage and Growth Company insignificant. With these results it can be said that the hypothesis is accepted ie Bankruptcy Prediction affect the provision of Going Concern Audit Opinion. Hypothesis 2 and 3 are not accepted, the Company’s Leverage and Growth does not affect the provision of Going Concern Audit Opinion .